2015
DOI: 10.1007/s11356-014-4045-7
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of leachate recirculation using vertical wells in bioreactor landfills

Abstract: Leachate recirculation (LR) in municipal solid waste (MSW) landfills operated as bioreactors offers significant economic and environmental benefits. The subsurface application method of vertical wells is one of the most common LR techniques. The objective of this study was to develop a novel two-dimensional model of leachate recirculation using vertical wells. This novel method can describe leachate flow considering the effects of MSW settlement while also accounting separately for leachate flow in saturated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Slimani et al (2017) conducted a leachate injection test using a vertical well with the injection flowrate of 3.5m 3 h −1 , and analyzed the leachate level using a mathematical model. In addition, the numerical simulation and mathematical calculation Temperature monitoring during a waterinjection test using a vertical well in a newly filled MSW layer of a landfill for leachate recirculation using a vertical well in a landfill have been carried out in various studies (Feng et al, 2015(Feng et al, , 2016a(Feng et al, , 2017a(Feng et al, , 2017bJain et al, 2010Jain et al, , 2014bKhire and Mukherjee, 2007;Reddy et al, 2013Reddy et al, , 2015; the injection flowrate of 0-55m³ d −1 was used among these works. From this literature, it is evident that leachate recirculation and liquid injection using a vertical well have been researched widely.…”
Section: Introductionmentioning
confidence: 99%
“…Slimani et al (2017) conducted a leachate injection test using a vertical well with the injection flowrate of 3.5m 3 h −1 , and analyzed the leachate level using a mathematical model. In addition, the numerical simulation and mathematical calculation Temperature monitoring during a waterinjection test using a vertical well in a newly filled MSW layer of a landfill for leachate recirculation using a vertical well in a landfill have been carried out in various studies (Feng et al, 2015(Feng et al, , 2016a(Feng et al, , 2017a(Feng et al, , 2017bJain et al, 2010Jain et al, , 2014bKhire and Mukherjee, 2007;Reddy et al, 2013Reddy et al, , 2015; the injection flowrate of 0-55m³ d −1 was used among these works. From this literature, it is evident that leachate recirculation and liquid injection using a vertical well have been researched widely.…”
Section: Introductionmentioning
confidence: 99%
“…We assessed the void volume with the bioreactor according to bed expansion. Void volume has previously been expressed as the dead volume in which there is no available access to cells [ 27 , 28 ], and a high void volume has an obvious effect on the mass transport between cells and the perfused solution [ 29 ]. We found that bed expansion in the DMFBB was significantly less than that in the conventional FBB, indicating the void volume was less in the DMFBB.…”
Section: Discussionmentioning
confidence: 99%
“…No DP, anomalous behaviour at the transition phases, IC. Feng et al (2013Feng et al ( , 2014Feng et al ( , 2015Feng et al ( , 2016Feng et al ( 2017a Investigate the hydrodynamic and biochemical behavior within a bioreactor landfill subjected to leachate recirculation.…”
Section: Slimani Et Al (2016)mentioning
confidence: 99%